Simple DNA sequences in homologous flanking regions near immunoglobulin VH genes: a role in gene interaction? - Cohen, J B (1982)
Five closely related immunoglobulin VH genes (subgroup II) were compared by sequencing of several kb of DNA. In three of the genes homology greater than 75% was found along an area of 4 kb that includes the coding region. The homology in flanking regions is only slightly lower than that in the coding sequences. Two other genes, which are located on the same EcoRI fragment, show high homology to the first three genes in the coding and immediately flanking regions. In more distant flanking regions no homology is found with the first three genes. This indicates that their evolutionary history differs from that of the other three genes. A region of simple DNA sequence composed of repetitive TCC and TCA elements was found at a distance of approximately 380 bp upstream from the initiator ATG of these VH genes. This region is the site where the two sets of genes abruptly start to diverge. The structure of the simple DNA sequence in the various VH genes suggests that it may be involved in gene interaction. We propose that both simple DNA sequences and homology in flanking regions serve a function in the correction of VH genes, which seem to be rather free to diverge and drift into pseudogenes. A correction mechanism may help this gene family to maintain its two major features, multiplicity and diversity.